Parsing the contributions of negative affect vs. aversive motivation to cognitive control: an experimental investigation - Yang, Qian; Si, ShuangQing; Pourtois, Gilles (Frontiers in Behavioral Neuroscience, 2023)
Introduction: Punishment is a powerful drive that fosters aversive motivation and increases negative affect. Previous studies have reported that this drive has the propensity to improve cognitive control, as shown by improved conflict processing when it is used. However, whether aversive motivation per se or negative affect eventually drives this change remains unclear because in previous work, the specific contribution of these two components could not be isolated. Methods: To address this question, we conducted two experiments where we administered the confound minimized Stroop task to a large group of participants each time (N = 50 and N = 47 for Experiment 1 and 2, respectively) and manipulated punishment and feedback contingency using a factorial design. These two experiments were similar except that in the second one, we also measured awareness of feedback contingency at the subjective level. We reasoned that cognitive control would improve the most when punishment would be used, and the contingency between this motivational drive and performance would be reinforced, selectively. Results: Both experiments consistently showed that negative affect increased at the subjective level when punishment was used and the feedback was contingent on task performance, with these two effects being additive. In Experiment 1, we found that when the feedback was contingent on task performance and punishment was activated, conflict processing did not improve. In Experiment 2, we found that conflict processing improved when punishment was contingent on task performance, and participants were aware of this contingency. Discussion: These results suggest that aversive motivation can improve conflict processing when participants are aware of the link created between punishment and performance.